(untitled) (One Health & Risk Management, 2025)
Introduction. The continuous evolution of the SARS-CoV-2 virus through the accumulation of genetic mutations has led to the emergence of variants with different characteristics, including increased transmissibility, heightened resistance, and changes in disease severity. Material and methods. The research was conducted using open-access international databases such as PubMed, Google Scholar, and national libraries, employing the keywords: SARS-CoV-2, COVID-19, genetic monitoring, mutation variants, sequencing, S. protein. Results. Currently, the WHO identifies five major genetic variants of concern (VOCs): Alpha, Beta, Gamma, Delta, and Omicron. The Alpha variant became globally dominant in early 2021 and was replaced by the Delta variant in the summer of 2021. The Delta strain has over 13 mutations, nine of which are found in the S protein. The genome of the Omicron variant contains more than 30 mutations in the conserved domain of the Spike protein. The Omicron variant caused a sharp increase in the number of COVID-19 cases worldwide and was responsible for a record 15 million new infections reported worldwide in one week. Conclusions. The continuous evolution of the SARS-CoV-2 genome poses new challenges for public health. It is essential to study the virus’s genetic characteristics to understand mutations, immune evasion, and the persistent effects of infection, with the aim of optimizing prevention and treatment strategies.